Systemic issues-structural organization of the autonomous Republic of Crimea - Лялюк, О. Ю. (Problems of legality, 2013)
The analysis of the nature of power in the Crimea, its main structural components are considered elements of the structure of government autonomy, interaction between them, as well as other sub-systems of power that operate in the ARC – the state and municipal. The main directions for improving systemic and structural organization of public power in ARC.